Pola Manajerial Zakat Dalam Perspektif Hukum Ekonomi Islam - Hilmi, Irvan; Rusli, Dodi Yarli; Pusvisasari, Lina; Athoillah, Mohamad Anton (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
his study intends to explain and examine the managerial patterns of zakat in the perspective of sharia economic law using qualitative methods, with a literature study approach. That zakat in a review of sharia economic law has strategic and significant potential. Therefore, zakat needs to get managerial attention that has a sense of alignment and is consistent with the mechanism of zakat according to syaari' instructions. In addition, the position of the state or in capacity as a government must of course guard it with all seriousness with the sharia mindset always being the basic motivation, so that the managerial pattern applied can function significantly to improve the welfare of society in a comprehensive manner. In this way, empowered zakat can be an alternative solution for people's welfare and a large source of state foreign exchange. So that zakat does not only have religious-spiritual value alone, but also zakat actually has an effective and useful economic value. Keywords: zakat, economic value, Islamid economic